THE POWER OF QIRĀ’ĀT: DISSECTING THE EPISTEMOLOGICAL POWER OF QIRĀ’ĀT IN THE INTERPRETATION OF THE QUR'ĀN - Abdul Jabar; Iqbal Salafuddin Zaini; Moh. Fadllurrahman; Azhar Ahmad Falahan; Abdur Rokhim Hasan (JOURNAL OF QUR'AN AND HADITH STUDIES, 2026)
This study examines the epistemological role of qirāʾāt in Qurʾānic interpretation, focusing on the maxim “baʿḍ al-qirāʾāt tuʾaththiru fī ikhtilāf al-tafsīr.” Unlike prior studies that mainly situate qirāʾāt within historical and transmission-based frameworks, this research adopts an integrative approach by repositioning qirāʾāt as an analytical instrument in tafsīr and legal derivation. The study employs a descriptive-analytical method on selected Qurʾānic verses. The findings reveal that qirāʾāt variations operate within a functional spectrum: some directly affect meaning and generate differences in legal, theological, and narrative interpretations, while others remain purely phonetic without interpretive impact. The main contribution of this study lies in conceptualizing qirāʾāt as a selective epistemological system, in which only certain variants produce interpretive differentiation. A limited “coding” analogy is employed to illustrate how micro-level changes in recitation may influence interpretive outcomes, although not all variations yield semantic effects. Thus, qirāʾāt is understood as a dynamic framework that preserves textual precision while enabling measured interpretive plurality.